2018
DOI: 10.1007/s10557-018-6774-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Review of the Pharmacogenomics of Direct Oral Anticoagulants

Abstract: As such, there is currently no strong evidence for the use of pharmacogenomic testing in optimizing the safety and efficacy of DOAC therapy. Nonetheless, genes of interest have been identified for each DOAC that may be of potential clinical utility. Further research is currently underway to elucidate the value of pharmacogenomics in this increasingly prescribed therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The influence of genetic factors on drug responses is complex, and genetic structure differences are thought to be the main factors leading to individual differences (Paré et al, 2013;Dimatteo et al, 2016;Rodríguez-Vicente et al, 2016). Genetic polymorphisms in a series of metabolic enzymes, transporters, receptors, and other drug targets involved in the process of drug delivery in vivo cause individual differences in drug efficacy and toxicity (Klein et al, 2017;Tseng et al, 2018). P-gp is an important transporter for many drugs in vivo (Choo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of genetic factors on drug responses is complex, and genetic structure differences are thought to be the main factors leading to individual differences (Paré et al, 2013;Dimatteo et al, 2016;Rodríguez-Vicente et al, 2016). Genetic polymorphisms in a series of metabolic enzymes, transporters, receptors, and other drug targets involved in the process of drug delivery in vivo cause individual differences in drug efficacy and toxicity (Klein et al, 2017;Tseng et al, 2018). P-gp is an important transporter for many drugs in vivo (Choo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was required that the patient’s genetic variant data were available from the biobanks. We analyzed genetic variants which have been identified in earlier research to be potentially associated with bleeding or thromboembolic events in DOAC users 7,8 …”
Section: Methodsmentioning
confidence: 99%
“…The effect of genetic factors on the pharmacokinetics of DOACs have been investigated in several studies 7–9 . Indications of association between genotypes and drug plasma levels have been found in some studies, 10–17 but also contradictory findings have been reported 5,18,19 …”
mentioning
confidence: 99%
“…Inter-individual variability in response to pharmacotherapy as well as molecular/physiologic "subtypes" of patients within the broad category of AD support the rationale for a personalized therapeutic approach based on unique genetic characteristics and individual lifestyle attributes (Hahn and Lee, 2019). There is growing interest in the use of pharmacogenomics to optimize the safety and efficacy of DOACs in anticoagulation therapy (Tseng et al, 2018). As more data using this approach become available, incorporating DOACs into a personalized precision medicine approach for the treatment of AD could be accomplished in the near future.…”
Section: Future Directionsmentioning
confidence: 99%